Impact of information technology on customer satisfaction: Special application to the post – conflict banking environment - Shivany, S.; Sanchieef, A. (My University, 2011)
Post conflict banking environment is exclusive, and furnishes opportunities for bankers to sell their services to the potential customers who have returned to their habitual life. The customers in the post conflict banking environment search for new innovative services to rebuild, and redevelop their buying. Because of the experienced gained in the conflict environment, consumers have become more knowledgeable, less naive, and less easily influenced, in addition they have more choices in the market. Bankers who attempt to penetrate their market in to post conflict marketing environment should select the appropriate factor for improving customer satisfaction level. The purpose of the study is to show the impact of the level of information technology and the level of customer satisfaction in the post conflict banking environment. The population of the present study consisted of local bank branches, which have adopted technology for their banking service that have been in operation in the post conflict banking environment, and the customers of those banks. Sample size of bank branches were 50 and the number of customer were 500 selected for the study. Multiple regression analysis, ANOVA, independent sample t-test, chi-square test, were used to test the conceptual model, with hypotheses testing procedure. The finding of this study shows that banks are implementing the modern technology at moderate level in the post conflict banking environment. Component of information technology such as ATM, online, mobile technology lead to improve the customer satisfaction. There are implications for practitioners, especially in local private commercial banking sector in the post conflict banking environment; it is importance to improve the usage of information technology (ATM, online, mobile technology), because these practices improve their customer satisfaction.
Keywords: Information technology; Customer Satisfaction; Post-conflict Banking environment